Disability support and reincarceration after a first adult prison custody episode for people with intellectual disability in New South Wales, Australia - Trofimovs, Julian (Journal of criminology, 2022)
Prisoners with an intellectual disability (ID) are an over-represented group in custody, with studies indicating this group is more likely to reoffend and be reincarcerated than the general prison population. While prisoners with ID share many of the same risk factors for recidivism as the general prison population, the lack of adequate disability support has been argued to be an additional key driver of recidivism for this group. This study aims to investigate reincarceration and factors associated with reincarceration after a first adult custody episode, including the impact of provision of general and specialist disability supports. The study used linked disability support services and custody data to identify a cohort of 1,129 prisoners with ID who were released from a first adult custodial episode in New South Wales (NSW) between 2005 and 2015. Over the follow-up period, the linked custody data showed that 72% (813) of those identified with an ID and released from a first adult custodial episode returned to prison, of which 76% (617) received no post-release disability support. This study found that 27% (308) of the study cohort had received a disability support service post-release from adult custody. Receipt of disability support was associated with a lower risk of reincarceration, while younger age and shorter duration of the custodial episode were associated with higher risk of reincarceration. The potential for disability support to lower risk of reincarceration highlights the importance of funding programmes that connect prisoners with ID to appropriate post-release disability supports.